PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN TERHADAP KINERJA APARAT PEMERINTAH DAERAH: BUDAYA ORGANISASI DAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MODERATING (Studi Empiris Pada SKPD Kota Malang) - Afdalul Aulad; Nur Hidayati; Junaidi Junaidi (Universitas Islam Malang, 2018)
ABSTRACTThis study aims to analyze and find out: 1) The influence of participationin budgeting on the performance of local government officials. 2) Organizationalculture can strengthen or weaken the influence of participation in budgeting onthe performance of local government officials. 3) Organizational commitment canstrengthen or weaken the influence of participation in budgeting on theperformance of local government officials.This type of research is quantitative. Research time starts from March toAugust. The population in this study is SKPD in Malang City Government. Thesample used in this study were 27 SKPD in Malang City Government withpurposive sampling technique. The data source used is primary data. Datacollection method uses a questionnaire that lists structured questions.The results of this study indicate that: 1) The results of a simultaneoussignificant test (statistical test F) showed that the participation of budgeting,organizational culture and organizational commitment had an effect on theperformance of the local government of Malang City. 2) The results of individualparameter tests (statistical test t) show that the participation of budgeting andorganizational culture influences the performance of the local governmentofficials in Malang City. While the organizational commitment does not affect theperformance of the local government of Malang City.Keywords: Performance of local government apparatus, participation inbudgeting, organizational culture, organizational commitment.